Are You Here? Psychotherapists’ Experiences of Embodied Relating in Teletherapy With Children During COVID-19: A Hermeneutic Literature Review - Hudson, Michelle Frances (Auckland University of Technology, 2022)
In response to the Sars-CoV-2 virus (COVID-19) pandemic, a significant and rapid increase in child teletherapy occurred. A compelling concern regarding teletherapy has been that access to implicit and nonverbal communications in teletherapy is altered or significantly reduced in comparison to face-to-face settings. However, research into psychotherapists’ subjective experiences of teletherapy is limited and further exploration has been widely recommended. In this hermeneutic literature review, I reviewed writing by psychotherapists in psychoanalytic and psychodynamic literature describing their experiences of teletherapy with children. I explored the research question: How did psychotherapists experience embodied relating in child teletherapy during COVID-19? Findings revealed that psychotherapists’ experiences of embodied relating were altered in the teletherapy setting in comparison to therapeutic settings with psychotherapists and children in the same physical location. These alterations were associated with a perceived loss by psychotherapists of their own vitality and of vitality in their relationships with children. Active efforts by psychotherapists were found to re-establish a sense of psychotherapists’ own embodied (including mind and body) awareness, and a restored sense of vitality and pleasure. Experiential training in embodied self-awareness in psychotherapeutic training programmes, in relation to the potential effects of teletherapy, would support practitioners in their clinical work in online contexts.